A novel and distributed three phase consensus based secured data sharing in internet of things environment - Rashmi H. Chamarajappa; Guruprakash C. Dyamanna (Institute of Advanced Engineering and Science, 2023)
The most essential part of any internet of things (IoT) model is the wireless sensor networks (WSN); latest technologies are combined with the applications of WSN results in fast, efficient, flexible as well as economical models. These networks are highly prone to attacks considering their characteristic nature, which includes self-organization, a topology that is dynamic, large-scale and constrained on the resources. Various models have been proposed for the detection of attacks in these wireless sensor networks. This research work proposes three-phase consensus based secured data sharing (TCSDS) in IoT environment. TCSDS adopts the consensus-based protocol for designing the security model in this research. Furthermore, TCSDS comprises three distinctive phases, each phase consisting of novel algorithm. First phase includes the setting up threshold value for sensor nodes. Second phase includes the efficient data packet transmission and third phase includes the efficient and secure routing, which tends to discard the unsecured nodes. TCSDS is evaluated considering the different parameter like energy consumption, malicious packet detection and throughput. Further comparison with the existing model is carried out based on the classified and misclassified packet; through the comparative analysis, it is observed that the TCSDS approach simply outperforms the existing model.